Problematika Sarana dan Prasarana Pendidikan - Rismayani Rismayani; Eliana Ayu Lestari; Nuraini Nindra Utami Br Tarigan (Al-Ulum: Jurnal Pendidikan Islam, 2021)
The problem of education that occurs in Indonesia is the problem of the lack of educational infrastructure, especially in remote areas. This is caused in the quality of education. There are so many students who cannot enjoy the same facilities and infrastructure as students in the city. This proves that the government pays little attention to the existing facilities in remote areas.This problem is usually caused by several factors, including the blocked allocation of funds because there are many situations where school funds must be used to make infrastructure for certain purposes. And another factor is poor maintenance which can happen because the school does not pay much attention to how to take care of the infrastructure that has been provided, indifference and lack of supervision from the government make many school facilities neglected. The results of the students were not comfortable using the facilities because many were damaged. Keywords: Problematics, Facilities, Infrastructure.